2016
DOI: 10.1177/1526602816664768
|View full text |Cite
|
Sign up to set email alerts
|

Tibiopedal Access for Crossing of Infrainguinal Artery Occlusions

Abstract: Purpose: To report a prospective, multicenter, observational study (ClinicalTrials.gov identifier NCT01609621) of the safety and effectiveness of tibiopedal access and retrograde crossing in the treatment of infrainguinal chronic total occlusions (CTOs). Methods: Twelve sites around the world prospectively enrolled 197 patients (mean age 71±11 years, range 41-93; 129 men) from May 2012 to July 2013 who met the inclusion criterion of at least one CTO for which a retrograde crossing procedure was planned or beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 22 publications
6
87
0
4
Order By: Relevance
“…The access failure rate for transpedal access in this study was similar to those previously reported and once access was obtained, the success rate of crossing the target lesion was 100%. The numbers of CTOs treated were higher in transpedal group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The access failure rate for transpedal access in this study was similar to those previously reported and once access was obtained, the success rate of crossing the target lesion was 100%. The numbers of CTOs treated were higher in transpedal group.…”
Section: Discussionsupporting
confidence: 88%
“…The use of ultrasound guidance and adaptation of transradial techniques such as use of vasodilatory medications, patent hemostasis technique for compression and use of low profile sheaths might contribute to these findings. Previous studies have also reported a similarly low complication rate with transpedal access . Despite advances in techniques and instruments, femoral access continues to have high access‐related complications .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…One of the challenges in endovascular interventions is lack of a real‐time hemodynamic measure, similar to FFR or iFR, to give functional and hemodynamic information of the severity. We and others have recently published several studies demonstrating that tibio‐pedal access for retrograde peripheral angiography and intervention is feasible, safe, and portend a low complication rate . Measuring pedal pressure from the tibio‐pedal access should be straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports have described the tibiopedal access for infragenicular and possibly infrainguinal endovascular interventions in patients with advanced peripheral vascular disease . Good technical success rate with low complication rate have been reported.…”
Section: Discussionmentioning
confidence: 99%